LITHUANIAN AND POLISH EXPERIENCE IN USING DIFFERENT METHODS IN THE STUDENT - CENTRED PROCESS (Mokslo taikomieji tyrimai / Applied Research, 2017)
This article intends to disclose Lithuanian and Polish experience in using different methods in student-centred process. The research methodology includes a critical survey of contemporary literature on student-centred studies. The most frequent student-centred methods are problem-based studies, project-led education, learning contracts, flexible studies, inquiry learning, just-in-time checking and personalised studies. The main method is to explain students why he/she was assessed in this way, and this provides students with a possibility to self-assess themselves and negotiate for grades.